(untitled) (International Seven Journal of Health Research, 2023)
VivaVôlei is a social project created by the Brazilian Volleyball Confederation (CBV), which covers more than twelve regions of Brazil, and its goal is the insertion of volleyball for children and adolescents in need, through the mini-volleyball methodology. The objective of this study was to verify, through a systematic review produced by means of articles published between the years 2003 and 2022, the quantity of publications about the project and whether they allude to its benefits for the target audience. Six scientific papers were found, five of them in Google Scholar in the form of articles published in journals, and one in the form of a book chapter found on the Capes platform. Satisfactory results were observed in the analyses, such as: socialization and happiness with the practice of sports, improvement in interpersonal relationships, progress in motor coordination, flexibility, and muscle strengthening. However, new studies about the program still need to be published